Sex-related differences in extracranial complications in patients with traumatic brain injury - Brandi, Giovanna; Gambon-Mair, Alma; Berther, Lara Selina; Bögli, Stefan Yu; Unseld, Simone (Frontiers in Neurology, 2023)
Background Extracranial complications after traumatic brain injury (TBI) are common. Their influence on outcome is uncertain. Furthermore, the role of sex on the development of extracranial complications following TBI remains poorly investigated. We aimed to investigate the incidence of extracranial complications after TBI with particular focus on sex-related differences with regard to complications and their influence on outcome. Methods This retrospective, observational study was conducted in a level I universitary swiss trauma center. Consecutive patients with TBI admitted to the intensive care unit (ICU) between 2018 and 2021 were included. Patients’ and trauma characteristics, in-hospital complications (i.e., cardiovascular, respiratory, renal, metabolic, gastrointestinal, hematological, and infectious) as well as functional outcome 3 months after trauma were analyzed. Data was dichotomized by sex or by outcome. Univariate as well as multivariate logistic regression was performed to reveal possible associations between sex, outcome and complications. Results Overall, 608 patients were included (male n = 447, 73.5%). Extracranial complications occurred most frequently in cardiovascular, renal, hematological and infectious systems. Men and women suffered similarly from extracranial complications. While men needed correction of coagulopathies more often (p = 0.029), women suffered more frequently from urogenital infections (p = 0.001). Similar results were found in a subgroup of patients (n = 193) with isolated TBI. A multivariate analysis did not show extracranial complications to be independent predictors of unfavorable outcome. Conclusion Extracranial complications following TBI occur frequently during the ICU-stay, can affect almost all organ systems but are not independent predictors of unfavorable outcome. The results suggest that sex-specific strategies for early recognition of extracranial complications might not be needed in patients with TBI.